A Theological Discourse on Church’s Response to Fundamentalist’s Assault on Her Mission and Members: The Nigerian Experience - Olaniyan, Gabriel Olatunde (KWASU Journal of Religious Studies, 2017)
How the Church should respond to violent attacks on her mission and members by those whose actions do not wish her well has been generating arguments because mission tasks is based on the love of God. Some Christians have argued that people should not respond to violence with violence based on biblical teachings, but majority of those who had experienced the bitter pill of attacks generally express contrary opinions. There seems to be a feeling that society needs a redefinition of biblical passages that teach on how to respond to attacks. The paper took a retrospective look at the paradoxical relationship existing between Christians and Muslims who profess one creator God and had common ancestry in Abraham. It also looked at some of the violent attacks on the Church particularly by the Boko Haram sect and some of the insinuations of a possible move by some governments in Nigeria to Islamize the country. To guide Christians in responding in a theologically appropriate manner the paper suggested self defense and adequate Christian education. It also recommended that churches should unite, teach converts to become intelligent believers who practice their faith reasonably. While not becoming offensive for any reason, they should be pro-active in their approach to self-defense against violent attacks.